Prevalence and Associated Factors of Depression, Anxiety, and Stress Among Hanoi Residents, Vietnam - Tuan, Ngo Tri; Hoai, Than Thu; Loan, Nguyen Thi; Duy, Nguyen Cao; Van, Hoang Thi Hai; Son, Dao Anh; Dat, Le Minh (Knowledge Dynamics, 2025)
Background: The increasing prevalence of stress, anxiety, and depression poses a greater risk, potentially amplifying complications and intensifying challenges across various aspects of public health. This study aims to evaluate the existing levels of stress, anxiety, and depression in individuals while analyzing key associated factors. Methods: 3840 residents of Hanoi city were selected for interview. An online questionnaire concerning psychological parameters, including the Impact of Depression, Anxiety, and Stress Scale-21 (DASS-21), was conducted. Statistical analyses were done using STATA version 15.0, with p-values under 0.05 considered significant. Results: The prevalence of depression, anxiety, and stress were 12.5%, 18.6%, and 10.6%, respectively. The rates of one symptom were 14.4%, two symptoms were 6.9%, and all three symptoms were 4.4%, respectively. There was a negative correlation with levels of depression, anxiety, and stress (adjOR (95%CI) =-0.2 (-0.22 - -0.17) – 0.12 (-0.15-0.09) – 0.09 (-0.13 - -0.06); p<0.01). Compared to men, women frequently experience higher levels of stress and anxiety. Married people experience lower levels of stress, anxiety, and depression compared to single people, and people who live in rural areas experience lower levels of depression than people who live in urban areas (adjOR (95%CI) = -0.04 (-0.07–0.01); p<0.01). Conclusions: The study provides evidence that people experience mental health problems such as depression, anxiety, and stress in Vietnam. There is a need for timely response measures to improve people's health and cope with different epidemic scenarios in the future.